Implementasi Model Waterfall dalam Aplikasi Manajemen Keuangan Berbasis Android - Niko Fernanda; Adityo Permana Wibowo (Journal of Information System Research (JOSH), 2025)
One of the main components in maintaining the stability and financial well-being of people and families is effective financial management. The myth that expenses will always increase along with income is one of the common misconceptions in society. This study aims to address this by creating financial management software for Android that facilitates effective and efficient financial management for users. The research methodology uses the waterfall model, which means that every step from needs analysis to implementation is completed systematically. The development process of this application utilizes Android Studio with the Kotlin programming language which is known to be efficient, while MySQL is used as a database for secure financial information management. The application system is designed using the Unified Modeling Language (UML) to define workflows and processes in a structured manner. The results of the application test use the blackbox testing method to test this application to ensure that all features such as recording financial information, income and expense transactions, and creating financial reports function as they should. In addition, this application also provides additional features in the form of investments to help users monitor their investment assets. From the tests carried out, all application features showed a success rate of 100%, indicating that the application functions according to the designed specifications. This application allows users to optimize financial management, so they can improve their standard of living in a more planned and systematic way.